THE EXPERIENCE OF MOLSIDOMINE USAGE IN PATIENTS WITH STABLE ANGINA PECTORIS - I. I. Sinitsina; V. A. Orlov; G. U. Zacharova; T. A. Gembitskaya (Столичная издательская компания, 2015)
Aim. To evaluate antianginal and antiischemic activity of molsidomine (Corvaton) in stable angina pectoris of II-III functional class (FC). Material and methods. 45 patients with II FC (31 persons) and III FC of angina (14 persons) were included into the study. All patients took molsidomine in individual doses during 3 months. Antianginal and antiischemic activity of molsidomine was estimated by veloergometric tests. Results. Molsidomine therapy resulted in disappearance of angina pectoris in 41, 7% of patients with stable angina of II-III FC and reduction of ST depression. Conclusion. Molsidomine is an effective antianginal and antiischemic medicine in patients with stable angina of II-III FC and provides the stable effect during long-term usage.